Designers The Key to Successful Product Development - Frankenberger, Eckart; Birkhofer, Herbert; Badke-Schaub, Petra (Springer London, 1998)
Modern product development means problem solving by teams in complex working environments. Thereby, the design process is influenced by factors from various fields, the task, the individual, the team, and the organisational context. This complex network of influences turns product development into a challenge with requirements for the designers aside from technical problems. This book contains the proceedings of the international symposium Designers - The Key to Successful Product Development held in Darmstadt, Germany, December 1997. During this meeting exponents from different leading research groups in engineering design came together to present and discuss their results. Within this volume different aims, issues and methods of design research are addressed in 23 contributions by different research groups. Structured in six sections according to the main fields of influence, it provides a survey of the state of scientifically-based knowledge and the trends of engineering design research on the influences leading to successful product development